Pusat Rekreasi Edukasi Pertanian Kacang Tanah Kabupaten Pati(Penekanan Arsitektur Tropis Ekspresionis) - Astuti, Dwi, Ir. Nurhasan, MT (2017)
Along the development era, the human needs grow including in terms of the need for recreation. Type of recreation as well as a means of learning is the main attraction for tourists, such as recreational and educational. Pati Regency is a regency in Central Java located in the Jalur Pantai Utara has a great potential in terms of tourism development sector. At present, the development of the tourism sector in Pati regency is still undeveloped, so we need a new innovation to improve the quality of tourism in Pati regency. Pati regency is famous for peanut agriculture, it can be used as a great potential to be developed as a means of recreational and educational activities. Recreational and agricultural education aims to introduce peanut farm in Pati regency to the people by bringing a variety of recreational activities and learning how to cultivate peanuts. By building a tourism region Recreation Center and Agricultural Education of Peanut in Pati Regency with the concept of tropical architecture expressionist, is expected the main attraction in the tourism sector in Pati Regency for tourist, more advanced and widely known.